Disparities in cancer care: Perspectives from the front line. Issue 3 (10th May 2013) - Miller, Patricia A.; Sinding, Christina; McGillicuddy, Patti; Gould, Judy; Fitzpatrick-Lewis, Donna; Learn, Linda; Wiernikowski, Jennifer; Fitch, Margaret I.
Abstract Objective: The purpose of this qualitative study was to investigate how frontline healthcare professionals witness and understand disparity in cancer care. Method: Six healthcare providers from a range of care settings, none with < 15 years of frontline experience, engaged with researchers in an iterative process of identifying and reflecting on equity and disparity in cancer care. This knowledge exchange began with formal interviews. Thematic analysis of the interviews form the basis of this article. Results: Participants drew attention to health systems issues, the meaning and experience of discontinuities in care for patients at personal and community levels, and the significance of social supports. Other concerns raised by participants were typical of the literature on healthcare disparities. Significance of results: Providers at the front lines of care offer a rich source of insight into the operation of disparities, pointing to mechanisms rarely identified in traditional quantitative studies. They are also well positioned to advocate for more equitable care at the local level.